Operational warfare at sea theory and practice - Vego, Milan N. (CASS series : naval policy and history, 2017)
This work explains and critically examines the main theoretical aspects of operational warfare at sea. It utilises diverse sources and examples from naval history, ranging from the ancient era to the present day, to present a comprehensive description and analysis of the key components of operational warfare at sea today. This book serves as a primer of how to plan, prepare and execute major naval operations and campaigns for naval commanders and their staffs, but will also be of interest to advanced students of naval history, strategic studies and military history in general.